Research on the Formation Mechanism of Loess Vertical Joints. (10th February 2021) - Wang, Chenxing; Jiang, Ruijun; Wang, Hong; Li, Tonglu; Kang, Haiwei; Hou, Xiaokun
Abstract : The popular occurrence of vertical joints in loess formation aggravates the anisotropism of loess and contributes to various geohazards (e.g., slope failures and soil erosion). To alleviate the geohazards caused by the vertical joints, researches need to be carried out to investigate the formation mechanism of these vertical joints. However, the theoretical analysis of the vertical joints' formation mechanism is limited up to now. In this study, we conducted a laboratory column experiment to observe joint development. Furthermore, using the unsaturated soil theory, we proposed a theoretical model to investigate the tensile stress that contributes to the formation of the loess vertical joint. In the experiment, the air-dried and crushed soil was sifted into the column, which simulates the free fall deposition process of the natural loess in China and contributes to a uniform state. 2500 ml of water was added at the top of the column. The topsoil experienced a wetting-drying process. During desaturation, 9 similar vertical joints were developed with similar horizontal distance. A theoretical model that calculates the interparticle force or tensile force between two adjacent particles was proposed based on the force balance equations. The theoretical model elucidates the phenomena in a laboratory experiment well and provides an insight into the formation mechanism of vertical joints in a uniform soil. The results highlight the generation of vertical joints in the initial deposition stage of loess with a uniform particle arrangement. Besides, the tensile force that contributes to the joint formation arises from the matric suction and surface tension of the solid-water-air contractile film.